Collective Bargaining in Provincial Public Administration - Christensen, Sandra (Relations industrielles / Industrial Relations, 1981)
It is the purpose of this paper to assess empirically the extent to which public sector pay rates closely track the private sector in response to cyclical changes in the economy, as measured by the rate of inflation and labour vacancy rates; and to determine whether the introduction of collective bargaining in the public sector has altered this relationship in any significant way.